Echocardiographic evaluation of mitral E/e′ ratio, along with angiographic findings and B-type natriuretic peptide levels as prognostic indicators in patients with ST-elevation myocardial infarction: A prospective cross-sectional study. - Kumar, Neeraj; Prasad, Ravi Vishnu; Kumar, Gautam (Student's Journal of Health Research Africa, 2025)
Background The approach to risk assessment in ST-Elevation Myocardial Infarction (STEMI) has evolved with advancements in echocardiographic and biochemical markers. The mitral E/e′ ratio and B-type Natriuretic Peptide (BNP) levels, along with coronary angiographic findings, offer a multidimensional approach to prognosis. Aim To evaluate mitral E/e′ ratio, BNP levels, and angiographic findings as prognostic indicators in STEMI patients. Methods A prospective, cross-sectional study was carried out at IGIMS, Patna, over 12 months (June 2024–May 2025). Fifty patients aged above 40 years diagnosed with STEMI were enrolled and followed up for six months. Echocardiography (including E/e′ ratio), BNP levels, and coronary angiography were assessed within 24 hours of admission. Follow-ups were conducted at 1 week, 3 months, and 6 months. Data were analyzed using SPSS v26.0. Results The participants' average age was 62.9 ± 10.8 years, and 68% of them were men. Among the most prevalent comorbidities were dyslipidemia (74%), diabetes mellitus (50%), and hypertension (54%). From 13.08 ± 3.21 at admission, the mean mitral E/e′ ratio decreased to 12.48 ± 2.47 at 1 week, 12.34 ± 2.10 at 3 months, and 12.12 ± 1.22 at 6 months (p < 0.001). From 1012.7 ± 890.4 pg/mL at admission to 195.1 ± 81.3 pg/mL at 6 months, BNP levels demonstrated a comparable progressive decline. Higher E/e′ and BNP levels were associated with worse outcomes, and in-hospital mortality was 14%. Conclusion Mitral E/e′ ratio, BNP level, and angiographic profile are effective prognostic tools in STEMI. Their integration enhances early risk stratification and individualized patient management. Recommendation Routine incorporation of mitral E/e′ ratio and B-type Natriuretic Peptide assessment, along with angiographic evaluation, is recommended for comprehensive prognostic evaluation and management of patients with ST-Elevation Myocardial Infarction.